أثر التنوع اللغوي في بلورة الوعي الثقافي المتعدد لدى المجتمع الواحد: The impact of linguistic diversity on the development of multiple cultural awareness in one community - مناصري, وفاء (Maalim, 2021)
Linguistic diversity plays its successful role in developing multiple cultural awareness among the members of the same community unless it is related to the perils of bilingualism that reject the centralization of the original language and cause tension in the unity of the self and the identity of man. The other is in the context of serving the original language and developing cultural bonds between peoples and nations, thus creating a responsible human consciousness towards the centrality of the mother tongue, preserving the self from the pitfalls of dispersion and disintegration and preserving its correct human and international position.